ANALISIS PERDAGANGAN INTRA INDUSTRI SEKTOR MANUFAKTUR INDONESIA DENGAN ASEAN-4: Berdasarkan Hipotesis Industry Specific dan Policy Based - DIAH WAHYUNINGSIH ; S.M. Kiptiyah,David Kaluge , Munawar Ismail
The objective of this study is, first, to identify the dominant manufacture_x000D_ products in intra industry trade of ASEAN-5 and Indonesia with ASEAN-4_x000D_ countries (Malaysia, Thailand, Philipina and Singapore). Second, to analyze_x000D_ factors that influence the level of intra industry trade of intra ASEAN-5 and_x000D_ Indonesia with intra ASEAN-4, based on industry specific and policy based_x000D_ hypothesis. Intra industry trade is measured by the use of Grubel and Lloyd_x000D_ indexes. Whenever the value of those two indexes are more than 40% then intra_x000D_ industry trade is happened, and if the value of those indexes is less than 40%_x000D_ then inter industry trade is occured._x000D_ Method of analyze in this study uses panel data with 19 industries as the_x000D_ cross-section data and the time period of the data is yearly data from 1998–2009._x000D_ This study is focused on the analyzing on the relationship of intra industri trade of_x000D_ intra ASEAN-5 and between Indonesia with other ASEAN-4 countries after_x000D_ decreasing tariff policy into 0% - 5% that is started in 2003._x000D_ The development of Indonesia intra industry trade in manufacture sector to_x000D_ intra ASEAN-5 market in 1998-2009 periods, based on ISIC category, showed a_x000D_ fluctuative movement. This condition shows an inconsistency of the_x000D_ competitiveness of the traded manufacture commodities. There are seven groups_x000D_ of industry with intra industri trade pattern that is consistent every year, they are